2009
DOI: 10.1124/dmd.109.027797
|View full text |Cite
|
Sign up to set email alerts
|

A Zone Classification System for Risk Assessment of Idiosyncratic Drug Toxicity Using Daily Dose and Covalent Binding

Abstract: ABSTRACT:The risk of idiosyncratic drug toxicity (IDT) is of great concern to the pharmaceutical industry. Current hypotheses based on retrospective studies suggest that the occurrence of IDT is related to covalent binding and daily dose. We determined the covalent binding of 42 radiolabeled drugs in three test systems (human liver microsomes and hepatocytes in vitro and rat liver in vivo) to assess the risk of IDT. On the basis of safety profiles given in official documentation, tested drugs were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
211
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(223 citation statements)
references
References 17 publications
7
211
1
1
Order By: Relevance
“…It is reported that the occurrence of IDT is related to clinical doses (Nakayama et al, 2009;Usui et al, 2009) and that IDT is rare with drugs at daily doses of 10 mg or less (Uetrecht, 1999). Therefore, we used the maximum daily dose in the analysis to distinguish the warning drugs from the withdrawn drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the occurrence of IDT is related to clinical doses (Nakayama et al, 2009;Usui et al, 2009) and that IDT is rare with drugs at daily doses of 10 mg or less (Uetrecht, 1999). Therefore, we used the maximum daily dose in the analysis to distinguish the warning drugs from the withdrawn drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the seminal work of Landsteiner and Jacobs (1935), who discovered a direct association between a chemical's propensity to bind covalently to protein and immune sensitization, it has been presumed that the formation of chemically reactive metabolites is the first step in the development of an IDR. It has been demonstrated that the risk that a drug will cause IDRs is roughly related to the amount of reactive metabolite that it forms (Nakayama et al, 2009). Therefore, attempts have been made to design the ability of a drug or a drug candidate to form a reactive metabolite out of the structure.…”
Section: Mechanistic Aspectsmentioning
confidence: 99%
“…It may take several weeks to months and repeated doses over a longer period until immune cells have proliferated and matured sufficiently in order to induce a clinically evident DILI. Recently, evidence has been presented that even complex mechanisms requiring repeated doses and interaction of several cell types may be predicted by relatively simple in vitro systems: considering both, protein binding of compounds to liver proteins and the daily dose of drugs allows a good differentiation between DILI inducing and negative compounds (Usui et al 2009;Nakayama et al 2009). Using this approach, the positive DILI compounds acetaminophen, alpidem, bromfenac, carbamazepine, diclofenac, flutamide, imipramine, nefazodone, tacrine, ticlopidine, tienilic acid, and troglitazone could be differentiated from negative compounds acetylsalicylic acid, caffeine, dexamethasone, losartan, ibuprofen, paroxetine, pioglitazone, rosiglitazone, sertraline, theophylline, venlafaxine, and zolpidem (Usui et al 2009).…”
Section: Idiosyncratic Drug-induced Liver Injury (Dili)mentioning
confidence: 99%